Rosa de capullos inviolados. El género discursivo sáfico en el siglo XIX y principios del XX - Galindo Santos, Alejandra (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
During the nineteenth and early twentieth centuries, the poet Sappho was setup to be a character in which in her making sensorial and erotic aspects or women were highlighted. Starting from the compilation of poems and plays where she is the main character, it is established as the discursive theme the feminine sensuality. Therefore, in this investigation it is proposed the conjunction of these as a Sapphic discursive genre, which based on their macropropositions diverge into Sapphic texts, dedicated to the amorous horizons of Sappho, and the Sapphism texts, these consist in the acknowledgement of the erotic and sexual pulsation of feminine voices alien to the poet. The Sapphic texts will be analyzed through a Systemic Functional Linguistics and its derivative Appraisal Theory, in which the poet transcends to modernity like a woman that enjoys her body as much as her intelligence; in turn, in the texts of Sapphism images with which the feminine desire is concealed are analyzed not as an object but as a sexual subject.

Durante el siglo XIX e inicios del XX la poeta Safo fue configurada como un personaje en cuya construcción resaltan los aspectos sensoriales y eróticos de la mujer. Partiendo de la recopilación de poemas y obras de teatro en los que la poeta es la protagonista, se establece como temática discursiva la sensualidad femenina. Por lo tanto, en esta investigación se propone la conjunción de estos como un género discursivo sáfico, los cuales según sus macroproposiciones se bifurcan en textos sáficos, dedicados a los horizontes amatorios de Safo, y los textos del safismo, consistentes en el reconocimiento de las pulsaciones eróticas y sexuales de voces femeninas ajenas a la poeta. Los textos sáficos se analizan a través de la Lingüística Sistémico Funcional y su derivada Teoría de la valoración en los que la poeta trasciende a la modernidad como una mujer que goza tanto del cuerpo como de su inteligencia; por su parte, en los textos del safismo se analizan las imágenes con que se encubre el deseo femenino no como un objeto sino como un sujeto sexual.
Facultad de Letras. Maestría en Estudios del Discurso
Keywords: info:eu-repo/classification/cti/4; FL-M-2024-0824; Safo; Discursos; Sensualidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18708